2002
DOI: 10.1292/jvms.64.1165
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Infection of Cats with Chlamydophila felis.

Abstract: ABSTRACT. Cats experimentally infected with a British isolate of Chlamydophila felis (C. felis), B166 strain, by droplet into the eye and nose developed conjunctivitis, mild rhinitis and fever. The chlamydophila were first isolated from conjunctiva, nictitating membrane and then from lung, tonsil, liver, spleen, kidney, nasal and vaginal swabs and blood. These results indicate that C. felis B166 strain first infected and replicated in the conjunctiva and nictitating membrane in cats with symptoms which were mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
1
6

Year Published

2005
2005
2020
2020

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(24 citation statements)
references
References 11 publications
0
17
1
6
Order By: Relevance
“…Latent infection and carrier status of C. felis in cats has also been postulated (14). C. felis has been isolated from the gastrointestinal tract, genital tract, lung, tonsil, liver, spleen, kidney, and blood (4,6,15). It has been shown that C. felis recovered from gastric mucosa of cats can induce ocular infection (1).…”
Section: Discussionmentioning
confidence: 99%
“…Latent infection and carrier status of C. felis in cats has also been postulated (14). C. felis has been isolated from the gastrointestinal tract, genital tract, lung, tonsil, liver, spleen, kidney, and blood (4,6,15). It has been shown that C. felis recovered from gastric mucosa of cats can induce ocular infection (1).…”
Section: Discussionmentioning
confidence: 99%
“…6,7 C felis mainly causes acute or chronic conjunctivitis and blepharospasm with serous or mucopurulent ocular discharge. [8][9][10] A presumptive diagnosis of the pathogen(s) involved in FURTD is commonly established based on the presence or absence of certain clinical signs; however, there is considerable overlap in clinical signs between the three pathogens, and mixed infections can occur. [11][12][13] As a consequence, the pathogens involved in FURTD can only be definitively identified by laboratory tests, which can be used to guide anti-infective treatment, such as antiviral drugs or antibiotics, and to control the infections in multicat households.…”
Section: Introductionmentioning
confidence: 99%
“…According to literature chlamydiosis in naturally infected cats usually begins on one eye (Masubuchi et al, 2002). Except patological changes on eyes, lack of weight gain and threadbarel fur, there were no other clinical signs of chlamydioses.…”
Section: Resultsmentioning
confidence: 99%